Dynamicity of perceived willingness to communicate, motivation, boredom and anxiety in Second Life: the case of two advanced learners of English. Issue 1 (27th January 2022) - Kruk, Mariusz
Abstract: The first part of the paper offers the characteristics of the affective variables of willingness to communicate, motivation, language anxiety and boredom as located within the framework of the complex dynamic systems. The second part aims to discuss the results of a study intended to examine the effect of Second Life on two English philology students' changes in the levels of willingness to communicate, motivation, language anxiety and boredom. The data collected via session logs underwent both quantitative and qualitative analysis. The results indicated changes in the levels of the variables in question both during single visits and from one visit to another. These changes in the constructs in question were affected by a number of positive (e.g. interesting topics, the possibility to discuss common interests, comprehending the output produced by interlocutors) and negative (e.g. unpleasant SL users, monotony, no willing to talk SL users, previous negative experience) factors.